Switched Aβ43 generation in familial Alzheimer’s disease with presenilin 1 mutation - Nobuto Kakuda (Nature Publishing Group, 2021)
Abstract Presenilin (PS) with a genetic mutation generates abundant β-amyloid protein (Aβ) 43. Senile plaques are formed by Aβ43 in the cerebral parenchyma together with Aβ42 at middle ages. These brains cause the early onset of Alzheimer’s disease (AD), which is known as familial Alzheimer’s disease (FAD). Based on the stepwise processing model of Aβ generation by γ-secretase, we reassessed the levels of Aβs in the cerebrospinal fluid (CSF) of FAD participants. While low levels of Aβ38, Aβ40, and Aβ42 were generated in the CSF of FAD participants, the levels of Aβ43 were unchanged in some of them compared with other participants. We sought to investigate why the level of Aβ43 was unchanged in FAD participants. These characteristics of Aβ generation were observed in the γ-secretase assay in vitro using cells, which express FAD mutations in PS1. Aβ38 and Aβ40 generation from their precursors, Aβ42 and Aβ43, was decreased in PS1 mutants compared with wild-type (WT) PS1, as observed in the CSF. Both the ratios of Aβ38/Aβ42 and Aβ40/Aβ43 in PS1 mutants were lower than those in the WT. However, the ratio of Aβ43/amyloid precursor protein intracellular domain (AICD) increased in the PS1 mutants in an onset age dependency, while other Aβ/AICD ratios were decreased or unchanged. Importantly, liquid chromatography–mass spectrometry found that the generation of Aβ43 was stimulated from Aβ48 in PS1 mutants. This result indicates that PS1 mutants switched the Aβ43 generating line, which reflects the level of Aβ43 in the CSF and forming senile plaques.